Wheat Straw Cellulose Amorphous Porous Carbon Used As Anode Material for a Lithium-Ion Battery - Yu, Kaifeng; Wang, Baoying; Bai, Peiming; Liang, Ce; Jin, Wenming (Journal of electronic materials, 2021)
Biomass-derived carbons are used efficiently in energy storage systems due to low cost, spacious distribution, and porous structure. Herein, we propose an uncomplicated method to prepare wheat straw cellulose porous carbon (WSCPC) using wheat straw cellulose as the carbon source and potassium hydroxide (KOH) as the activation agent. A series of characterizations are performed on six samples treated with different amounts of activator. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirm that WSCPC-4 (4:1 mass ratio of activator to carbon) has an abundant pore structure over the surface, with a high surface area of 628 m 2 g −1 . Furthermore, a reversible capacity of 1420 mAh g −1 at 0.2 C is obtained after 100 cycles. These results indicate that wheat straw porous carbon provides an effective method for designing high specific capacity electrode materials. Graphic Abstract